2019
DOI: 10.1101/800151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MetAP2 inhibition reduces food intake and body weight in a ciliopathy mouse model of obesity

Abstract: The ciliopathies Bardet-Biedl Syndrome and Alström Syndrome are genetically inherited pleiotropic disorders with primary clinical features of hyperphagia and obesity. Methionine aminopeptidase 2 inhibitors (MetAP2i) have been shown in preclinical and clinical studies to reduce food intake, body weight, and adiposity. Here we investigated the effects of MetAP2i administration in a mouse model of ciliopathy produced by conditional deletion of the Thm1 gene in adulthood (Thm1 cko). Thm1 cko mice show decreased hy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Tesofensine, a serotoninnoradrenaline-dopamine monoamine reuptake inhibitor was co-administered with metoprolol (to reduce blood pressure) and showed that it could inhibit hunger feeling and food cravings by boosting the three neurotransmitters' activity. Meanwhile, Beloranib inhibits an enzyme methionine aminopeptidase 2 (MetAP2) that reduces hunger and induces weight loss (45). While JD5037, a cannabinoid-1 receptor blocker reacts on CB receptors function in inhibiting food intake and increasing satiety.…”
Section: Advantagesmentioning
confidence: 99%
“…Tesofensine, a serotoninnoradrenaline-dopamine monoamine reuptake inhibitor was co-administered with metoprolol (to reduce blood pressure) and showed that it could inhibit hunger feeling and food cravings by boosting the three neurotransmitters' activity. Meanwhile, Beloranib inhibits an enzyme methionine aminopeptidase 2 (MetAP2) that reduces hunger and induces weight loss (45). While JD5037, a cannabinoid-1 receptor blocker reacts on CB receptors function in inhibiting food intake and increasing satiety.…”
Section: Advantagesmentioning
confidence: 99%